2004
DOI: 10.3748/wjg.v10.i17.2553
|View full text |Cite
|
Sign up to set email alerts
|

Heparin improves organ microcirculatory disturbances in caerulein-induced acute pancreatitis in rats

Abstract: Heparin administration has a positive influence on organ microcirculatory disturbances accompanying experimental Cn-induced acute pancreatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…Another important features in the course of pancreatitis is the drop in microperfusion in the pancreatic gland, which in turn could enhance the infl ammatory state. Dobosz et al [29] have demonstrated that heparin improved pancreas microcirculation in rats with cerulean-induced pancreatitis. In this failure, participate vasoactive mediators such as endothelin, nitric oxide and bradykinin [30] .…”
Section: Discussionmentioning
confidence: 99%
“…Another important features in the course of pancreatitis is the drop in microperfusion in the pancreatic gland, which in turn could enhance the infl ammatory state. Dobosz et al [29] have demonstrated that heparin improved pancreas microcirculation in rats with cerulean-induced pancreatitis. In this failure, participate vasoactive mediators such as endothelin, nitric oxide and bradykinin [30] .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, studies in rats showed that heparin administration in experimental acute pancreatitis improved both pancreatic microcirculation and the inflammatory response (reduction in leukocyte-endothelium interaction). 74,75 Moreover, anticoagulant treatment with heparin seems to reduce platelet entrapment in the lungs during acute pancreatitis. 76 On the other hand, the role of heparin in postYendoscopic retrograde cholangiopancreatography (ERCP) pancreatitis is still unclear.…”
Section: Pathophysiology Of Hemostatic Disorders In Acute Pancreatitimentioning
confidence: 99%
“…to affect the development of microcirculatory disturbances in experimental acute pancreatitis [4,7,12,13,15,19,31,36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Although the role of microcirculation disturbances in the pathogenesis of acute pancreatitis is well known [5,13,16,18,23,32,41,44], there are only limited number of studies dealing with general hemorheological or micro-rheological changes [e.g., 4,6,7,20]. In the development of microcirculatory disturbance in severe acute pancreatitis numbers of cytokines, inflammatory mediators and reactive oxygen species play role [4,8,12,14,21,23,26,32,34,36,37,42,43].…”
Section: Introductionmentioning
confidence: 99%